Analisis Makna Kias dalam Puisi “Guru” Karya Muhammad Asqalani Eneste: Kajian Semantik - Dita Puspita Junaedi; Kartika Kartika; Fatmawati Fatmawati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to examine the figurative meanings in the poem "Guru" by Muhammad Asqalani eNeSTe through a semantic approach. The poem portrays the struggle and dedication of a teacher who devotes themselves to serving in a remote area with deep love and sacrifice. This research adopts a qualitative method with content analysis techniques by conducting a document study of the poem's text. The analysis reveals that the poem is rich in figurative language, including metaphor, personification, hyperbole, metonymy, synecdoche, and simile. Each of these figures of speech is employed to depict the social, emotional, and spiritual conditions of the teacher and the environment in which they serve. The use of figurative meaning in the poem not only beautifies the language but also strengthens the moral messages, educational values, and appreciation of the teaching profession. By understanding these figurative meanings, readers can grasp deeper humanistic and simplicity values embedded in the realm of education.